(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2025)
This study presents a systematic review of measurement scales for employee turnover intention, focusing on identifying validated instruments suitable for public service contexts and Spanish-language environments. Through an analysis of papers indexed in the WoS and Scopus databases, we identified and evaluated four primary measurement scales: the staying/leaving index (Bluedorn, 1982), Hom and Griffeth’s 1-item scale (1998), the Crossley 5-item scale (2007), and the proximal withdrawal states scale (Hom et al., 2012). The review encompassed analysis of theoretical frameworks, methodological approaches, and validation studies, with special attention paid to construct validity and cross-cultural adaptations. Our findings indicate a historical evolution from simple, direct measurement approaches to multi-dimensional frameworks. The comparative analysis of scale items revealed varying approaches to temporal framing and response formats, with implications for measurement accuracy and practical utility. While traditional scales focus primarily on immediate leaving intentions (the focus in this paper), newer instruments incorporate broader contextual factors and motivational states. However, we identified a significant gap in validated Spanish-language instruments and public sector-specific measures. This review provides a foundation for selecting appropriate measurement tools and highlights the need for further validation studies in specific cultural and organizational contexts.